Educational Efforts to Improve Public Awareness about Greening and Healthy Lifestyle in Urban Areas - Shereen Aprillia; Jolene Budiono; Meiliyana Wijaya (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
Public awareness and concern about greening and healthy lifestyles in preserving the environment and improving health status are crucial despite the covid-19 pandemic. One approach to deal with this issue is by spreading the information and taking promotive actions which aim to increase public awareness of the importance of greening and healthy lifestyles in their daily lives. Various online educational activities for communities are needed to increase their knowledge and concern. In this regard, the Daerah Binaan (DABIN) unit and the Hazard Analysis and Critical Control Point (HACCP) of the Faculty of Medicine and Health Sciences at Atma Jaya Catholic University of Indonesia held a SEHATI challenge and an educational seminar "Evergreen: Go Green, Go Healthy." One of the topics raised through this online seminar was "Urban Farming in the Pandemic Period: Economical and Ecological," which discusses various benefits of growing hydroponic vegetables. In addition, the topic of promoting a healthy lifestyle includes the proper processing of fresh vegetables to avoid parasitic contamination and a healthy breakfast with the consumption of probiotics. As many as nine and 198 people attended the challenge competition and seminar. A pre-test and a post-test were held before and after the seminar to determine the participants' knowledge. The result showed that the participants' knowledge increased between 15% to 38%. The efforts to deliver periodic education about greening and healthy lifestyles action will continue to be carried out by DABIN and HACCP. These efforts aim to improve public awareness about the importance of this topic, reduce global warming, and improve the health status of an area.